IMPACT OF AGRICULTURAL PRODUCTION ON GROSS DOMESTIC PRODUCT IN THE REPUBLIC OF SERBIA - Zelenović , Vera; Grubor , Aleksandar; Zelenović, Jelena; Vučić, Vladan (Economics of Agriculture, 2023)
The goal of this research is to quantify the influence of each segment of agricultural production individually on the formation of the total gross domestic product in Serbia. For the purposes of the research, the gross domestic product at the level of Serbia, expressed at current prices, was used as the dependent variable. On the other hand, the values of agricultural production (plant production, vegetable production and horticultural products, livestock production, production of livestock products, and agricultural services) expressed also in current prices were observed as independent variables. The research used regression analysis. The most important result of this research is that plant production is recommended as the dominant direction of Serbian agriculture, given that its influence is most pronounced when it comes to the formation of the value of agricultural production, and therefore the total gross domestic product of Serbia.